The Role of Human Capital in Increasing Productivity and Growth of MSMEs: A Systematic Literature Review - M.Ridho Saputra; Nurfitriana; Tedi Purnama; Immarotul Ummah; Relasari (PT. Maju Malaqbi Makkarana, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a very strategic role in the global economy as the backbone of the economy that contributes significantly to economic growth, improving the quality of human capital is a key factor in encouraging productivity and economic growth, including in the MSME sector. This research aims to identify, evaluate, and systematically synthesize empirical and conceptual findings related to the role of human capital in increasing the productivity and growth of MSMEs. This study examines the role of human capital in increasing productivity and growth for MSMEs using the Systematic Literature Review (SLR) approach. A total of 30 indexed and peer-reviewed scientific articles published in the period 2020 to 2026 were systematically analyzed by following the PRISMA guidelines. This study focuses on four main human capital instruments, namely Resource Based View, Dynamic Capability, and Value Co-Creation as fundamental elements in increasing productivity and growth for MSMEs. The results of the synthesis show that most of the studies identified a positive relationship around 80% of the studies analyzed identified a positive relationship between the application of human capital in increasing productivity and growth of MSMEs, both directly and through the role of mediation and moderation variables. However, not all studies show consistent results. The other 20% of articles showed non-positive results, which included insignificant, conditional, mixed, or negative findings